Membedah Diskursus Modal Sosial dan Gerakan Sosial: Kasus Penolakan Pabrik Semen di Desa Maitan, Kabupaten Pati - Priyatno Harsasto (Program Magister Ilmu Politik, Universitas Diponegoro, 2020)
Social capital is a result of social movement and vice versa. Social movement’s theories such as the mobilization of resource model tries to explain the anatomy of collective action in the context of liberal political system in the West. These theories can be used to dechiper collective action in general but may be not enough to explain rural social action in Indonesia which under transitional democracy political regime. In present rural Indonesia, social movement participated by “weak” groups of peasants break out most frequently. These peasents movements are against local governments or enterprises who distupt citizens’ rights. The civic protest against semen enterprise in Maitan Village in Pati District is the case in point. The social networks created thecollective action. However, the horizontal networks among protesters themselves cannot be succesful without the help of vertical network such as support that they may have received from high-ranking officials in the local government bureaucracy.